Semi-interpenetrating polymer networks of poly (vinyl alcohol)-functionalized nanocrystals/sulfonated poly (ether ether ketone) (PVA-FNCs/SPEEK) as fuel cell membrane. (December 2021) - Malik, Rajender Singh; Soni, Udit; Chauhan, Sampat Singh; Kumar, Devendra; Choudhary, Veena
Abstract: Proton conducting membranes of poly (vinyl alcohol) - functionalized nanocrystals/sulfonated poly (ether ether ketone) PVA-FNCs/SPEEK were synthesized by solution casting. SPEEK (DS 70%) was mixed with calculated amount of PVA/FNCs solution by keeping ratio of PVA: FNCs constant (98.8: 1.2 (w/w %)) and Thermal cross-linking was done in a vacuum oven at various temperatures 100 °C (2 h), 120 °C (2 h), 130 °C (2 h) and 140 °C (2 h) to form semi-interpenetrating polymer network membrane. Formation of semi-interpenetrating (SIPN) network was established by FTIR studies, water uptake and dynamic mechanical analysis (DMA). SEM and XRD analysis were carried out for morphological parameters. Synthesized membranes showed good proton conductivity range of 10 −2 to 10 −3 S/cm at 100% relative humidity. Membranes based on PVA-FNCs and SPEEK (30:70, w/w) (XPVA/SP-70) showed maximum conductivity i.e. 14 mS/cm and 8.66 mS/cm at 80 °C and 25 °C respectively. Glass transition temperature of engineered membranes was found to be higher than pure SPEEK and XPVA. Increment in storage modulus on addition of SPEEK in the temperature range of 300–25 °C confirming the formation of network structure or increased rigidity. Fuel cell performance of SIPN membranes based MEA was studied with hydrogen and oxygen gas fuel at 50 °C and found maximum power density of 182.6 mW/cm 2 for XPVA/SP-70. A systematic study of SIPN membranes with relative proportion of SPEEK and degree of cross-linking of PVA-FNCs were key factors to establish the optimum properties. Graphical Abstract: ga1